Optimalisasi Penerapan Budaya Keselamatan dan Kesehatan Kerja (K3) Melalui Peran igeneration Dalam Mewujudkan Zero Accident di Tempat Kerja: A Systematic Literatur - Fatliana, Anggun Nindy; Hidayatullah, Anung Andi; Maulana, Yusuf; Hatala, Muhammad Hudzaly; Acitra, Rina; Nuraeni, Intan; Nurhalizah, Alya Adha (Jurnal Kalibrasi, 2025)
The need for competent human resources (HR) is crucial in facing the challenges of the industrial revolution 4.0. The iGeneration generation, as a digital native generation, has significant potential in encouraging the strengthening of the Occupational Safety and Health (OHS) culture towards achieving zero accidents. This study aims to analyze the strategy for optimizing OHS culture through the role of iGeneration with a qualitative approach based on Literature Review. The results of the study indicate that workers' understanding of OHS culture is still low and compliance with standard operating procedures (SOPs) is not optimal. iGeneration plays a role in building technology-based innovations, such as accident detection systems, education through digital videos, interactive OHS applications, game-based virtual training, and collaboration on digital work platforms. This initiative contributes to increasing OHS awareness and can be a strategic indicator for achieving zero accidents in the workplace.